2011
DOI: 10.1177/2158244011413474
|View full text |Cite
|
Sign up to set email alerts
|

Return and Volatility Spillovers Among Asian Stock Markets

Abstract: The study examines the return and volatility spillover among Asian stock markets in India, Hong Kong, Japan, China, Jakarta, and Korea using a six-variable asymmetric generalized autoregressive conditional heteroscedasticity–Baba, Engle, Kraft, and Kroner (GARCH-BEKK) model during February 2, 2007, to February 29, 2010. The author finds evidence of bidirectional return, shock, and volatility spillover among most of the stock markets. The magnitude of volatility linkages is low indicating weak integration of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 25 publications
4
39
0
2
Order By: Relevance
“…The studies on developing equity markets include studies, for example, Mukherjee and Mishra (2010), Joshi (2011), Choo et al (2011, and Sakthivel and Kamaiah (2011). Mukherjee and Mishra (2010) empirically examined volatility transmission of equity market of India with 12 selected equity markets (China, Malaysia, Sri Lanka, Thailand, Indonesia, Pakistan, Malaysia, Korea, Hong Kong, Sri Lanka, Taiwan, and Japan).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The studies on developing equity markets include studies, for example, Mukherjee and Mishra (2010), Joshi (2011), Choo et al (2011, and Sakthivel and Kamaiah (2011). Mukherjee and Mishra (2010) empirically examined volatility transmission of equity market of India with 12 selected equity markets (China, Malaysia, Sri Lanka, Thailand, Indonesia, Pakistan, Malaysia, Korea, Hong Kong, Sri Lanka, Taiwan, and Japan).…”
Section: Review Of Literaturementioning
confidence: 99%
“…By applying the GARCH model, they found evidence of bidirectional return spillover between India and all selected markets except Sri Lanka. Joshi (2011) empirically examined the spillover of return and volatility between Asian countries (Korea, China, India, Indonesia, Hong Kong, and Japan). By applying the GARCH BEKK model, he found bidirectional return spillover in the following markets: Indonesia and China, Korea and Japan, India and Hong Kong, and Hong Kong and Korea.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported different results but a number of studies reveal co-movements of international stock markets. For instance, [13] detected bi-directional in returns, shocks and volatilities among Asian countries. [7] detected two-way directional volatility spillovers between U. S. and Indian stock market through trade and investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reference [19] used BEKK framework and observed volatility spillover among almost all Asian stock markets. Reference [29] detected significant volatility spillover across all Gulf stock markets using BEKK GARCH.…”
Section: Literature Reviewmentioning
confidence: 99%